2008
DOI: 10.1073/pnas.0801068105
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a BK channel auxiliary protein controlling molecular and behavioral tolerance to alcohol

Abstract: Tolerance, described as the loss of drug effectiveness over time, is an important component of addiction. The degree of acute behavioral tolerance to alcohol exhibited by a naïve subject can predict the likelihood of alcohol abuse. Thus, the determinants of acute tolerance are important to understand. Calcium-and voltage-gated (BK) potassium channels, consisting of pore forming ␣ and modulatory ␤ subunits, are targets of ethanol (EtOH) action. Here, we examine the role, at the molecular, cellular, and behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 45 publications
7
92
2
Order By: Relevance
“…It has been shown that BK-␤4 is predominantly expressed in the brain and alcohol modulates BK-␣/␤4. 35 Therefore, a neural defect of Kcnmb4 Ϫ/Ϫ , in which the mice are drinking excessively, should be considered. We observed a moderate but significant increase in water consumption in the Kcnmb4 Ϫ/Ϫ .…”
Section: Na K and Volume Balance In Ka Kcnmb4mentioning
confidence: 99%
“…It has been shown that BK-␤4 is predominantly expressed in the brain and alcohol modulates BK-␣/␤4. 35 Therefore, a neural defect of Kcnmb4 Ϫ/Ϫ , in which the mice are drinking excessively, should be considered. We observed a moderate but significant increase in water consumption in the Kcnmb4 Ϫ/Ϫ .…”
Section: Na K and Volume Balance In Ka Kcnmb4mentioning
confidence: 99%
“…Moreover, data from both recombinant and native BK channels (reviewed in Brodie et al, 2007) demonstrate that ethanol modulation of BK NPo is concentration dependent, with an EC 50 of ∼20 mMthat is, close to the blood alcohol level that constitutes legal intoxication in the US (17.4 mM)-and E max 100 mM, a concentration corresponding to a blood alcohol level that may be fatal in ethanol-naïve mammals (Diamond, 1992). Remarkably, the modulation of BK activity by brief exposure to ethanol concentrations ,100 mM has been reported to contribute to a wide variety of alcohol actions in mammals, including inhibition of vasopressin and oxytocin release from neurohypophysial nerve endings, antinociception via drug action on primary sensory dorsal root ganglia neurons, decreased excitability of nucleus accumbens neurons, aortic and cerebral artery constriction, endothelial proliferation, and neuroprotection against ischemic-reperfusion injury (Liu et al, 2004;Brodie et al, 2007;Martin et al, 2008;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on recombinant BK proteins expressed in heterologous systems and native channels in their natural cell environment have both consistently documented that the channel steady-state activity or NPo, i.e., the product of the number of ion channels in the membrane (N) and the channel open probability (Po), is drastically modulated by acute exposure to 50 mM ethanol (Brodie et al, 2007;Martin et al, 2008;Wynne et al, 2009). This concentration is reached in blood during moderate-toheavy alcohol intoxication (Diamond, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly the Drosophila slowpoke gene appears to contain a binding site for CREB (cyclic-AMP response element binding protein) which has been implicated in learning and memory and hence may also be involved in the ethanol response (Cowmeadow et al, 2006) and possibly in the memory deficits after excessive alcohol intake. Further experimentation into the molecular mechanism of tolerance using single channel recoding revealed that only after expression of the somatic BK -subunit together with the brain specific 4-subunit ethanol dosedependently increased the open probability of channels and decreased the duration of action potentials whereas BK -subunit together with the ß1-subunit expressed in dendrites was insensitive to ethanol Martin et al, 2008) Human BK channels (hslo) are also potentiated by alcohol being dependent on the presence of auxiliary -subunits (Feinberg-Zadek & Treistman 2007). BK channel activity containing only the -subunit were substantially increased by ethanol, together with the 4-subunit the channel mean open time was also increased but to a lesser extent and channel activity was unaffected in the presence of 1-subunit.…”
Section: Bk Channels -And Ethanol Tolerancementioning
confidence: 99%
“…The experiments clearly demonstrate that mutation of a single gene affects ethanol sensitivity, although this is most probably not the only mechanism involved and it remains interesting to further monitor extensions of these findings to higher animals or to humans. Martin, et al (2008) recently examined the generation of action potentials in brain spiny neurons using whole cell patch clamp recordings. They found that the number of action potentials evoked by current injection was increased in 4-subunit knockout mice compared to wild type under the influence of ethanol.…”
Section: Bk Channels -Ethanol and Behaviourmentioning
confidence: 99%